Combination of Green Marketing and Green Products on Purchasing Decisions J. Co Donuts & Coffee (Forward Joint Branch) Katamso Medan - Sartika, Gita Suci; Syahriandy, H.; Marbun, Patar (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The combination of Green Marketing and Green Products on purchasing decisions for J.CO Donuts & Coffee (Maju Bersama Branch" is the topic of this research. This type of research is quantitative. The generalization area consists of objects or subjects that have certain qualities and characteristics applied by researchers, with an average of 427/month. People are the research population. This research uses a purposive sampling technique, which requires selecting samples based on predetermined standards. The number of samples in this research is 81 people which is determined using the Slovin formula. SPSS 26 is used in this research to process data, such as instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. According to hypothesis testing, it is used to individually test the significance of the relationship between the independent variable and the dependent variable with an alpha value = 0.05%.